2022
DOI: 10.1007/s11325-022-02629-8
|View full text |Cite
|
Sign up to set email alerts
|

BASH-GN: a new machine learning–derived questionnaire for screening obstructive sleep apnea

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…This explains the superior performance of SLEEPS in comparison to previously developed OSA or insomnia screening questionnaires that were based on LR. Furthermore, we found that distinguishing COMISA from OSA is critical for accurate prediction (Table S2 in Multimedia Appendix 1 ), unlike previous studies [ 25 , 26 , 30 , 31 , 33 , 35 ] where COMISA and OSA were not distinguished. Specifically, the model’s performance decreased when merging the COMISA and OSA labels.…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…This explains the superior performance of SLEEPS in comparison to previously developed OSA or insomnia screening questionnaires that were based on LR. Furthermore, we found that distinguishing COMISA from OSA is critical for accurate prediction (Table S2 in Multimedia Appendix 1 ), unlike previous studies [ 25 , 26 , 30 , 31 , 33 , 35 ] where COMISA and OSA were not distinguished. Specifically, the model’s performance decreased when merging the COMISA and OSA labels.…”
Section: Discussioncontrasting
confidence: 86%
“…In contrast to previous OSA screening studies [ 25 , 26 , 30 , 31 , 33 , 35 ], we separated COMISA from OSA. To investigate the importance of this separation, we merged COMISA with OSA to create a new OSA label and retrained the XGBoost model predicting this label using the SMC training set.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations